Swift-XRT and NuSTAR Monitoring of Obscuration Variability in Mrk 477 - N. Torres-Albà; Z. Hu; I. Cox; S. Marchesi; M. Ajello; A. Pizzetti; I. Pal; R. Silver; X. Zhao (The Astrophysical Journal, 2025)
We present the analysis of 15 X-ray observations of Mrk 477, a nearby Seyfert 2 active galactic nucleus, with the objective to monitor its obscuring column density variability. The full data set consists of five archival observations, split into two XMM-Newton, two NuSTAR and one Chandra observation, plus two dedicated monitoring campaigns. The monitoring campaigns were performed with Swift-XRT and NuSTAR, containing five observations each. We performed a simultaneous analysis using self-consistent torus models, deriving geometric properties of the torus as well as the obscuration along the line of sight. Mrk 477 is best modeled with a torus with a large covering factor yet low column density (on average). Its line-of-sight column density oscillates between 1.5 and 7 × 10 ^23 cm ^−2 . Mrk 477 presents frequent obscuring column density variability, on timescales as short as ∼2 weeks. The probability of drawing a pair of obscuration-variable observations for Mrk 477 when having two, three, and four observations is 40%, 78%, and 95%, respectively. Adding the results of this work to those of another 26 sources, we find a trend of increasing obscuration variability with time (from ∼20% at Δ t  < 10 days, to ∼60%–70% at timescales larger than 5 yr). We discuss whether this is compatible with the majority of obscuration variability coming from broad-line region clouds.